Evaluating water conservation and water demand management in an industrialised city: a case study of the City of uMhlathuze in Richards Bay - Mthethwa, Nkosinathi I (Urban Management, 2018)
The objective of this study was to evaluate water conservation and water demand management in an industrialised City of uMhlathuze in Richards Bay. The City of uMhlathuze Local Municipality is the third-largest municipality in KwaZulu Natal (KZN) and is strategically placed to continue attracting investment as an aspirant metropolis due to the newly established Industrial Development Zone (IDZ) and the country's largest deep-water port. As an industrialised city, uMhlathuze's demand for water is already increasing and with the establishment of the IDZ, it is expected that water demand will escalate even further once the IDZ is fully operational. In line with the research question, this study has, therefore, sought to understand whether the industrialised City of uMhlathuze has developed and effectively implemented a water conservation and water demand management strategy and interventions in order to sustain water supply in anticipation of growing demand due to industrialisation and population growth. This objective was achieved by evaluating the city's current interventions and measures using a range of water conservation and water demand management solutions and guidelines. During this study, it was evident that the greatest threat facing South Africa's ambitious future economic growth, poverty alleviation and government's transformation agenda was the inefficient and unbalanced use of available and limited water resources. Thus, in order to avoid this imminent threat, the country as a whole must continuously reduce water consumption and demand from various sectors. This goal can be achieved through sustainable and improved water conservation and water demand management interventions. The study found that, in recent years, the issue of water scarcity had escalated in KZN. The province was in the grip of a drought, which was taking its toll on water supply in various municipalities around the province. The sparse rainfall in most parts of the province had caused the levels of rivers and dams to decrease to a point of crisis. Consequently, the KZN Provincial Government declared the province a disaster area in 2015. During the study, there was very little improvement as the City of uMhlathuze was still subjected to level 4 water restrictions. Evidently, the drought was intensifying the water problem in a municipality already grappling with poor and inadequate water infrastructure. A review of international and local literature was undertaken to theoretically position the objective of the research. An evaluation of the City of uMhlathuze water conservation and water demand management strategy and interventions was conducted using a questionnaire completed by city officials and part of the study included documentation review. This study investigated key elements of water conservation and demand management as well as interventions that were pertinent to achieving the desired outcome of efficient use of water. Respondents were required to answer questions focusing on several water conservation and water demand management related approaches and solutions. During the study, it was identified that there were inconsistencies in the implementation of water conservation and water demand management interventions even though the City of uMhlathuze had already taken the important step of developing a water conservation and water demand management strategy. It was recognised, however, that water conservation and water demand management remained relatively new for most municipalities. Consequently, it would take time for municipalities, together with communities, to implement effective interventions. The focus needs to be on the establishment of a combined team of staff and stakeholders, set up to finding solutions and interventions designed to maximise the most sustainable and efficient use of water. The conclusions drawn from this study and proposed recommendations indicated that wastewater reuse; pipe replacement; water pressure management; rainwater and stormwater harvesting; water sensitive urban design; leak detection and repair; joint planning and research team with the Industrial Development Zone; groundwater and aquifer recharge; stakeholder engagement, education and citizen awareness are feasible options for the City of uMhlathuze to consider in relation to water conservation and water demand management. These solutions should constitute the foundation of a revised and updated water conservation and water demand management strategy to be implemented incrementally with broad-based participation.